If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(x + 1.2) + 10 = 24 Reorder the terms: -5(1.2 + x) + 10 = 24 (1.2 * -5 + x * -5) + 10 = 24 (-6 + -5x) + 10 = 24 Reorder the terms: -6 + 10 + -5x = 24 Combine like terms: -6 + 10 = 4 4 + -5x = 24 Solving 4 + -5x = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -5x = 24 + -4 Combine like terms: 4 + -4 = 0 0 + -5x = 24 + -4 -5x = 24 + -4 Combine like terms: 24 + -4 = 20 -5x = 20 Divide each side by '-5'. x = -4 Simplifying x = -4
| s-10=20.37 | | 8x+14=8x-19 | | 8x+14=-4x-19 | | 6.1=-logx | | -9y+-1[2(1+3y)+6]=5y | | -3x+3=4x-18 | | 2h+7=65 | | 7(r+6)=34 | | 3[5+-3(x+-4)]=2x+9 | | 3(1+-2c)+-4=-2(3c+-1) | | 2(x+8)=2(x+11) | | 3(1-2c)-4=-2(3c-1) | | -9x+3=-x+99 | | -3x^2+13x-4= | | q=c-d | | 2-(m-30)=-6m | | 6y-2[7(1y+1)+4]=10y | | 8x+15=-4x+63 | | 12a-6+8=2 | | -3x^2+13-4= | | 15x-10=9x+26 | | 4d+d=40 | | x^2+11x+2= | | 6+-1(8-4m)=2(2m-1) | | 3x+9=6x+4 | | x^2-36x=8140 | | 8(x-.75)+12=-10 | | 1-4n=29 | | F(x)=13x+7 | | -1x-3=-2x-4 | | 5-(8+10)=8+5 | | 10+4q=34 |